Innate immune recognition of breast tumor cells mediates CCL22 secretion favoring Treg recruitment within tumor environment - Ménétrier-Caux, Christine (Landes Bioscience, 2012)
Regulatory T cells (Treg) have been reported of poor prognosis for overall survival in primary breast tumors (BT). As CCL22 plays a major role in Treg recruitment within primary BT we deciphered the mechanisms involved in the CCL22 production by breast epithelial tumor cells and propose herein the major role of their innate immune recognition in this production.